Synthesis Of TiO2 Nanoparticles And Characterization Of Sn-3.0Ag-0.5Cu/TiO2 Via Nanoindentation And Selective Electrochemical Etching - Yahaya@Kamaluddin, Muhamad Zamri (2018)
Distributions of incorporated TiO2 nanoparticles in the Sn-3.0Ag-0.5Cu (SAC305) solder alloy were investigated by nanoindentation and selective electrochemical etching. Optimum size of the TiO2 reinforcement particles were obtained by the sol-gel centrifuge precipitation method. The SAC305-TiO2 composite solder was successfully blended by the aid of ball milling. Increment on the TiO2 weight percentage significantly refined the morphologies of the SAC305-TiO2 composite solder. Excessive TiO2 addition of 1.5 wt. % induced a reduction on the hardness value. The highest hardness performance was obtained for the SAC305-TiO2 composite solder with 1.0 wt. % of incorporated reinforcement particles. The hardness profiles indicate the dominant distribution of the TiO2 nanoparticles near the solder/substrate interfaces. The optimum SAC305-TiO2 composite solder attained slightly better electrochemical behavior with higher recorded current. Increment on the etching time mainly improved the observation on the shape profile and size refinement of the Cu6Sn5 and Ag3Sn IMC. Etching time up to 150 s deteriorates the morphologies of the IMC phase due to excessive removal of the Sn. Observation on the TiO2 nanoparticles were obtained by higher magnification on the micrographs with optimum etching time of 120 s. Clusters of the TiO2 nanoparticles were observed to cling onto the Cu6Sn5 IMC layer. Higher calculated mass and volume of the Sn removal were attained by the SAC305-TiO2 composite solder due to much favorable dissolution induced by the refinement on the morphologies.